Glycated haemoglobin A1c for diagnosing diabetes in Chinese subjects over 50 years old: a community‐based cross‐sectional study. (9th April 2013) - Lin, Shuo; Hu, Li; Li, Xiaofeng; Chen, Yanming; Xu, Haixia; He, Shengqing; Ren, Zhuozhuo; Tang, Xixiang; Qiu, Yawei; Xu, Jing; Mu, Panwei; Zeng, Longyi
Summary Objective Little is known about using glycated haemoglobin A1c (HbA1c) to diagnose diabetes in Chinese subjects over 50 years old. This study aims to evaluate HbA1c in diagnosing diabetes and identify the optimal threshold to be used in Chinese community subjects aged over 50 years. Methods A community‐based cross‐sectional survey was conducted from October 2010 to January 2011 in Shipai community of Guangzhou, Guangdong, China. A total of 1494 subjects (72·8%) aged over 50 years were investigated. Fasting plasma glucose (FPG1st) and HbA1c were assayed in each participant. Diabetic candidates with FPG1st ≥ 5·6 mmol/l or HbA1c ≥ 39 mmol/mol (5·7%) were informed to undergo a 75‐g oral glucose tolerance test (OGTT). Diagnosis of diabetes was made by 1999 World Health Organization criteria. Sensitivity and specificity of HbA1c for diagnosing diabetes were calculated by receiver operating characteristics (ROC) curve. Results Among 1494 subjects, 161 subjects (10·8%) with previously diagnosed diabetes and 21 with missing data were excluded. Among the remaining 1312 subjects (87·8%), 861 subjects (65·6%) with either FPG1st ≥ 5·6 mmol/l or HbA1c ≥ 39 mmol/mol (5·7%) were invited to perform OGTT. Finally, 453 subjects (52·6%) performed OGTT (FPG2nd and 2‐h plasma glucose were measured) and 54 subjects (11·9%) were identified as being diabetes. The area under ROC curve was 0·916 (0·887–0·940) for HbA1c and 0·972 (0·953–0·985) for FPG2nd in diagnosing diabetes (P = 0·045). An HbA1c threshold of 48 mmol/mol (6·5%) yielded the highest combination of sensitivity (75·9%) and specificity (95·5%) for diagnosing diabetes. Conclusion An HbA1c threshold of 48 mmol/mol (6·5%) was highly specific and had a good sensitivity for diagnosing diabetes among Chinese subjects aged over 50 years with FPG ≥ 5·6 mmol/l or HbA1c ≥ 39 mmol/mol (5·7%). This threshold may be suitable for diagnosing diabetes in Chinese subjects over 50 years old.